Visualization of a lost painting by Vincent van Gogh using synchrotron radiation based X-ray fluorescence elemental mapping - Dik, Joris; Janssens, Koen; Van der Snickt, Geert; van der Loeff, Luuk; Rickers, Karen; Cotte, Marine (Analytical chemistry (Washington), 2008)
Vincent van Gogh (1853-1890), one of the founding fathers of modern painting, is best known for his vivid colors, his vibrant painting style, and his short but highly productive career. His productivity is even higher than generally realized, as many of his known paintings cover a previous composition. This is thought to be the case in one-third of his early period paintings. Van Gogh would often reuse the canvas of an abandoned painting and paint a new or modified composition on top. These hidden paintings offer a unique and intimate insight into the genesis of his works. Yet, current museum-based imaging tools are unable to properly visualize many of these hidden images. We present the first-time use of synchrotron radiation based X-ray fluorescence mapping, applied to visualize a woman's head hidden under the work Patch of Grass by Van Gogh. We recorded decimeter-scale, X-ray fluorescence intensity maps, reflecting the distribution of specific elements in the paint layers. In doing so we succeeded in visualizing the hidden face with unprecedented detail. In particular, the distribution of Hg and Sb in the red and light tones, respectively, enabled an approximate color reconstruction of the flesh tones. This reconstruction proved to be the missing link for the comparison of the hidden face with Van Gogh's known paintings. Our approach literally opens up new vistas in the nondestructive study of hidden paint layers, which applies to the oeuvre of Van Gogh in particular and to old master paintings in general.